Export credit insurance and guarantees : a practitioner's guide - Salcic, Zlatko; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
The first practitioner handbook on export credit insurance and guarantees, providing manufacturers, exporters, bankers, and lawyers with a much needed resource. The book contains descriptions and analyses of almost every type of export credit insurance and guarantee used in international trade with explanations about the risks inherent in each.
Keywords: Credit insurance; Investment guaranty insurance